Turkish PASE: Turkish Version of the Psoriatic Arthritis Screening and Evaluation Questionnaire - Oyur, Kadir Berat (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2014)
BACKGROUND: Psoriatic arthritis (PsA) is an inflammatory arthritis associated with psoriasis and causes irreversible joint damage, unless detected early and treated with systemic drugs. OBJECTIVE: There is no reliable tool for screening PsA among Turkish psoriasis patients. Therefore, we aimed to validate the psoriatic arthritis screening and evaluation (PASE) questionnaire in the Turkish. METHODS: A 15-item Turkish PASE questionnaire was administered to 122 consecutive psoriasis patients who visited our dermatology clinic for routine evaluations. Then, the patients were evaluated for PsA by a rheumatologist who was blinded to the results of the questionnaire. RESULTS: Among the 113 patients who participated in the study, 11.5% (13 of 113) had a diagnosis of PsA. The Turkish PASE total scores ranged from 15 to 67 (possible range, 15~75). The median total score was 49 (25th and 75th percentile, 36 and 50) for the PsA group and 35 (25th and 75th percentile, 27 and 42) for the non-PsA group. The median total score of the PsA group was significantly higher than that of the non-PsA group (p=0.33). The Turkish PASE total score of 44 distinguished PsA from non-PsA participants, with 62% sensitivity and 76% specificity. For further analysis of each question, we counted the responses according to symptoms (positive for "agree" and "strongly agree" and negative for "disagree" and "strongly disagree"), and the sensitivity ranged from 23% (third question of the functions subscale) to 77% (second question of the symptoms subscale, first and fifth questions of the functions subscale) and the specificity ranged from 51% (second question of the symptoms subscale) to 87% (fourth question of the functions subscale). No relation was found between the PASI scores and the presence (p=0.899) or absence (p=0.941) of PsA, as well as between the PASI and PASE scores of each patient (p=0.961). CONCLUSION: Thirteen of the 15 items demonstrated significant test-retest reliability as assessed with the Spearman correlation coefficient (p<0.05). These results show that the Turkish version of the PASE questionnaire may be useful for identifying PsA patients for inclusion in trials; however, it is not a reliable tool for screening PSA patients in a dermatology clinic.